Parkinson's disease does not alter automatic visual-motor coupling in postural control - Cruz, Caio Ferraz (2018)
This study examined the coupling between visual information and body sway in patients with Parkinson's disease (PD) compared with healthy controls. Postural control performance was compared between 14 patients with PD (age: 69.6 +/- 8.8 years - stages 1-3 of the Hoehn and Yahr scale) and 14 healthy control participants (age: 68.6 +/- 3.0 years). Participants stood upright in a moving room that remained motionless or continuously oscillated in the anterior-posterior direction. Ten trials were performed in the following conditions: no movement of the room (1 trial) and with the room moving at frequencies of 0.1, 0.17, and 0.5 Hz (3 trials each frequency). Body sway and moving room displacement were recorded. The results indicated that patients with PD displayed larger body sway magnitude in the stationary room condition. Body sway of patients with PD was induced by visual manipulation in all three visual stimulus frequencies, but body sway of patients with PD was less coherent compared to that of the control participants. However, no difference was observed in the visualbody sway coupling structure. These results indicate that patients with PD can unconsciously couple body sway to visual information in order to control postural sway in a similar manner to healthy participants with intact visual-motor coupling for posture control. However, this coupling is marked by greater variability, indicating that people with PD have a motor system with greater inherent noise leading to a more varied behavior.